Analysis Color Control LED (Light Emitting Diode) On Traffic Light Revolution - Pratama R A; Febrianti M S (International Conference on Engineering and Technology Development (ICETD), 2017)
The issue of transportation in various forms is one of the main problems faced by the world's cities, including cities in Indonesia. Vehicle growth, increased traffic intensity of goods and services as well as increased user population associated disproportionate availability of roads and supporting facilities resulted in a wide range of crucial issues. Where lead to reduced effectiveness and efficiency of the transportation system in support of the mobility of society. Traffic congestion is one of the main problems in the transportation system. Based Data Transport Statistics 2013 & 2014 are sourced from statistics Indonesia (BPS Catalog: 8301007) cite an increase in the number of vehicles is high at 10.39 per cent per year on all types of vehicles. Coupled with the specific transportation community awareness so that adds a level of congestion becomes worse. Signs and traffic lights play an important role in regulating the traffic lane so that the public transport can be wise in using the road, especially in the port city of Lampung.